Potentiation of the anti-inflammatory effects of NSAIDs, steroids and statins using antioxidants - Ahmed, Tanvir (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.